KEBIJAKAN FORMULASI HUKUM PIDANA TERHADAP MALE RAPE DALAM PEMBAHARUAN HUKUM PIDANA BERDASARKAN NILAI KEADILAN - Anis Widiyanti (UNISSULA, 2014)
The Impact of globalization facility access of foreign cultures, including ease of access to the means of pornography and pornographic, resulting in the absence of a strong handle on life, causing rape behavior. Rape itself is usually synonymous with women as victims and men as perpetrators. In fact, men can be victims of rape and women are able to become actors. Positive criminal law that applies in Indonesia contains the definition of rape is too shallow. In the legislation in Indonesia implements rape sex offenders must be a male and a female rape must be victim. This of course is loaded with elements of discrimination because it does not include the various forms of rape that occurred in the community. The protection of victims of crime of rape cannot be separated from the consequences experienced by the victim after the rape that happened. Victims not only suffered financial losses and social losses, but also suffered physical and psychological suffering that needs to be formulated on the formulation of criminal law reform regarding criminal offenses of rape based on the value of justice.